Predictors of Piano Student Dropouts - Gerelus, Karen; Comeau, Gilles; Swirp, Mikael (Intersections)

(untitled) (Canadian University Music Society / Société de musique des universités canadiennes, 2017)
Dropping out of piano lessons before reaching a moderate mastery of the instrument is a frequent problem among students. Previous research finds that children often leave music lessons as the result of predictors such as expertise—measured by musical ability, academic achievement, and musical achievement—and environment—measured by social and educational status, gender differences, parental involvement, and home culture. Fifty-five former piano students and their parents filled out questionnaires with Likert-scale, multiple choice, and open-ended questions in a mixed-methods study. This group was compared to 153 students and parents who were still involved with lessons. The results between the two groups show that many of the attrition factors outlined in the literature predicted piano student dropouts as well.